The role of marketing citizenship in enhancing the reputation of the organization / Study of the views of a sample of employees in private hospitals - Ahmed Azan Shareef (Zanco Journal of Humanity Sciences)
The research focuses on identifying the role of the dimensions of marketing citizenship, namely, the economic dimension, the legal dimension, the moral dimension and the human dimension, in enhancing the organization’s reputation for a sample of hospitals operating in the city of Erbil, through field testing of research variables based on theoretical framework. Methodological.